Analisis Budaya Sekolah Sebagai Faktor Penentu Karakter Siswa di MTsN 2 Kota Blitar - Vina Aulia Permata; Dita Hendriani (Lembaga Pengembangan Kinerja Dosen, 2024)
The application of school culture is important in forming student character, therefore researchers conducted an analysis of school culture as a determining factor in student character. This research was conducted at MTsN 2 Blitar City because this school is a school with potential and excellence. The problem that researchers found both outside the classroom and inside the classroom was that there were still a lack of students who obeyed and understood school culture so that this became a form of habit in breaking the rules. From the results of these observations, the researcher obtained several problem formulations, namely; 1. What is the state of school culture at MTsN 2 Blitar City, 2) What is the character of the students at MTsN 2 Blitar City, 3) What is the relationship between school culture and student character at MTsN 2 Blitar City. This research is included in qualitative research with descriptive methods. Data collection by researchers used observation, interview and documentation techniques. The data obtained will be qualitative data, in the form of observations and short interviews. The results obtained by researchers are that the state of school culture at MTsN 2 Blitar City is very creative and innovative. However, it turns out that this is still not enough to build student character. This is caused by two internal factors, namely those originating from oneself, and external factors originating from the external environment.